Modernization of electricity rates in Costa Rica – towards the path of efficiency - Gómez, Roberto Jiménez (2023)
Costa Rica’s regulatory framework enabled the universalization and sustainability of the electricity system. The task ahead for the regulatory body and stakeholders in the sector is to achieve efficiency that translates into lower rates. The objective of this article is to assess the actions taken by the regulatory agency in the period 2016-2022 to take the sector towards the path of efficiency and to provide forward-looking considerations on the remaining tasks. To this end, it examines the context, the actions taken and their impact on the rates paid by users. The evidence shows that the measures adopted by the regulatory body in that period improved the efficiency of the sector and halted the upward trend in prices in 2019. On the other hand, it argues that, in the context of the new realities of a fast-evolving sector, the search for efficiency calls for changes in the approach to regulation, the role of regulated entities and assertive governance. Distribution companies must adopt a commercial approach to the services they provide, in line with the new realities, particularly the competition that technology introduces into the sector. There is a need for a regulation that is flexible, enables the adoption of new technology and is forward looking, as well assertive governance of the sector that includes comprehensive planning and optimization of the electric system with the objective of reducing its long-term costs and ensuring its sustainability.